Biocompatible and biodegradable zeolitic imidazolate framework/polydopamine nanocarriers for dual stimulus triggered tumor thermo-chemotherapy. (April 2018) - Wu, Qiong; Niu, Meng; Chen, Xiaowei; Tan, Longfei; Fu, Changhui; Ren, Xiangling; Ren, Jun; Li, Laifeng; Xu, Ke; Zhong, Hongshan; Meng, Xianwei
Abstract: Zeolitic imidazolate frameworks (ZIFs) have attracted great interest as pH-sensitive drug carrier because of high drug loading and intrinsic biodegradability. In this work, a biocompatible NIR and pH-responsive drug delivery nanoplatform based on ZIFs (PDA-PCM@ZIF-8/DOX) is synthesized for in vivo cancer therapy. The biocompatibility of ZIFs is greatly improved by polydopamine (PDA) modifying and proved by cytotoxicity and in vivo acute toxicity evaluation. The degradability is also regulated in an appropriate rate. Due to mild reaction condition of ZIFs, the synthesis and drug loading is achieved in one pot with high loading (37.86%) and encapsulation rate (78.76%). Meanwhile, PDA acts as a photothermal transfer agent to trigger thermal response switch of phase change materials for NIR controlled drug release. Under the dual stimulus of NIR and acid environment, the drug release is as high as 78%, while only 21% is released without stimulus, showing a remarkable effect of control release. In vivo anti-tumor experiments demonstrate the high tumor inhibition rate of photothermal-chemotherapy group with a significant synergistic effect. The biocompatible and biodegradable drug delivery platform based on ZIFs has shown great promise for future clinic cancer therapy.